Miniaturization with Dumbbell Shaped Defected Ground Structure for Power Divider Designs Using Sonnet - Mahouti, Peyman; Belen, Mehmet Ali; Partal, Hakan Pasa; Demirel, Salih; Gunes, Filiz (IEEE, 2015)
In this article, a power divider (PD) with dumb-bell shape defected ground structure (DGS) is investigated for miniaturization purpose. The proposed dumbbell shaped DGS are placed in the ground plane of a microstrip power divider. Firstly, a PD without DGS had been designed and simulated in Sonnet Suits environment to have the results for benchmarking. After that, DGS had been implemented under the transmission lines in output port for investigating the effect of the DGS to the design. It had been found that by adding DGS it not only reduced the size of the design, but also there are some improvements in performance compared to the design without DGS. Simulation results had been verified with the measurement results given in manufacturing and measurement section.
Keywords: Defected Ground Structures; Miniaturization; Power Divider; Sonnet; LINE; Engineering